FSH suppression and tumour control in patients with prostate cancer during androgen deprivation with a GnRH agonist or antagonist. (2nd November 2018) - Crawford, E. David; Tombal, B.; Keane, T.; Boccardo, F.; Miller, K.; Shore, N.; Moul, J. W.; Damber, J.-E.; Collette, L.; Persson, B.-E.
Abstract: Background: Gonadotropin releasing hormone (GnRH) antagonists suppress follicle-stimulating hormone (FSH) to lower levels than GnRH agonists. This may partially explain the differences between these agents on prostate cancer outcomes. In this post-hoc analysis, FSH and prostate specific antigen (PSA) responses and the impact of cross-over from leuprolide to degarelix were evaluated from a 1-year comparative study (CS21) and its extension study (CS21A). Materials and methods: Overall, 610 patients were enrolled in CS21, wherein PSA and FSH levels were evaluated monthly. CS21A evaluated 386 patients, including those previously treated with degarelix ( n = 251) who continued to receive degarelix, and those previously treated with leuprolide ( n = 135) who crossed-over to receive degarelix. PSA and FSH levels were evaluated in CS21A for 3 months after cross-over. The associations between measurements were assessed using Spearman's correlation coefficient. The impact of class variables on FSH suppression were evaluated using Analysis of Variance. Results: Rapid PSA and FSH suppression was observed and maintained in the degarelix arm (CS21 and CS21A), while patients on leuprolide experienced rising PSA during CS21. Patients crossed-over from leuprolide to degarelix achieved a suppression of FSH and a significant PSA decrease. PSA and FSH levels were significantly ( p < .05) correlated at months 1, 3, 6, 12 and 13 in the degarelix arm. Conclusions: Significant FSH suppression with GnRH antagonists may explain its advantage over GnRH agonists in terms of better prostate cancer control. The effect of profound FSH suppression is analogous to the need for profound testosterone suppression for tumor control.